2015
DOI: 10.1088/0031-9155/60/24/9215
|View full text |Cite|
|
Sign up to set email alerts
|

Potential role of the glycolytic oscillator in acute hypoxia in tumors

Abstract: Tumor acute hypoxia has a dynamic component that is also, at least partially, coherent. Using blood oxygen level dependent (BOLD) magnetic resonance imaging (MRI), we observed coherent oscillations in hemoglobin saturation dynamics in cell line xenograft models of head and neck squamous cell carcinoma. We posit a well-established biochemical nonlinear oscillatory mechanism called the glycolytic oscillator as a potential cause of the coherent oscillations in tumors. These data suggest that metabolic changes wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Tumor glycolysis can oscillate under certain conditions, which has been demonstrated in cells that develop a hypoglycemic phenotype [7][8][9]. This phenomenon is verified through temporary oscillations in the concentration of glycolytic intermediates.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…Tumor glycolysis can oscillate under certain conditions, which has been demonstrated in cells that develop a hypoglycemic phenotype [7][8][9]. This phenomenon is verified through temporary oscillations in the concentration of glycolytic intermediates.…”
Section: Introductionmentioning
confidence: 87%
“…The variation of the control parameter C showed that the sustained periodic behavior occurs in a range of glucose input rate limited by two critical values (0,02 and 0,15 mM min -1 approximately). According to Fru et al [8] this oscillatory domain could be within the physiological range. Values of C less than the lower limit or greater than the upper limit lead the system to a stable steady state.…”
Section: Characterization Of the Autonomous Systemmentioning
confidence: 92%
See 2 more Smart Citations
“…Also, Baudelet, et al [13] showed periods of approximately 20 minutes using the BOLD-MRI technique. We have previously demonstrated the presence of cyclic hypoxia with a regular periodicity in a bladder cancer xenograft [14,15].…”
Section: Introductionmentioning
confidence: 96%